Global Sensitivity Analysis for the Elastic Properties of Unidirectional Carbon Fibre Reinforced Composites Based on Metamodels. Issue 3 (March 2018) - Zhu, Chao; Zhu, Ping; Lu, Jiahai
A fast and effective numerical method to predict mechanical properties of carbon fibre reinforced polymer (CFRP) composites, even elastic properties, is complicated due to the mismatch of mechanical properties among the constituents. Furthermore, it is not possible to completely characterise the influence of multiple parameters including mechanical and structural parameters on the bulk properties of CFRP by experiments. In this study, a three-phase finite-element model consisting of matrix, carbon fibre and interface was developed to predict the elastic mechanical behaviour of unidirectional CFRP. The elastic properties in terms of two Young's moduli, two Poisson's ratios and a shear modulus were calculated by means of a homogenisation method. High-accuracy Kriging surrogate models were constructed to fast-calculate the elastic responses for a large number of samples. Combining Kriging and high-dimensional model representation (HDMR) methods, a global sensitivity analysis was performed to study how the microscopic parameters influence the elastic responses to get a deeper understanding of elastic property-structure relationship. Eleven parameters, including mechanical and geometry properties of constituent phases, were chosen as inputs. Independent and cooperative effects of input parameters on the elastic properties of the studied composites were surveyed via first- and second-order sensitivity indices, respectively. An importance ranking of these parameters for each elastic response was derived directly by these indices. The procedure proposed in this work could serve as a theoretical guide for further design optimisation of CFRP.